EDITOR’S NOTE (JOURNAL OF INDIAN EDUCATION, 2010)
The National Focus Group on Teaching of Science (NCERT, 2005) observes a huge gap in the education in general and science education in particular between the rural and urban students. The inequality, among other things may be mainly due to poor infrastructure, inadequate support systems, lack of access to information and other resources in rural areas, and a clean urban bias in various educational inputs. The focus group points out that in terms of content rural life styles need to be reflected in the curriculum, which can be done very effectively in contextualised curricula. In the present issue, our three contributors viz., Arvind Gupta, Shashi Prabha and K. Abdul Gafoor and Smitha Narayan take up the issue of science education in Indian schools and deliberate upon it through their writings.